Dinamika Izin Operasional Mie Gacoan di Bulan Ramadhan: Implementasi Perda No.13 Tahun 2003 dan Dampaknya bagi Konsumen serta Pelaku Usaha di Banjarmasin - Afifah, Lintang Laila Gina; Aufa, Muthia Rahida; Hashifah, Rania Alma; Anggrainnie, Siska Nur Ayu (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
The 24-hour operation of dining establishments during Ramadan requires special attention due to consumer demand for meal services during sahur and iftar, as well as government regulations regarding business operating hours. This study employs a case study method by examining the operational permits of dining establishments in a major city in Indonesia that enforces specific policies during Ramadan. The focus of this research is to analyze how these policies are implemented, their impact on business owners, and consumer reactions to the prevailing regulations. On the other hand, government policies restricting the operating hours of restaurants and food stalls during fasting hours in Ramadan aim to respect the practice of fasting and maintain social order. This study seeks to analyze how Mie Gacoan responds to these policies and adjusts its operations to meet consumer needs while complying with the applicable regulations. The findings indicate that Mie Gacoan’s success in managing operational permits during Ramadan heavily depends on its strategies for adjusting opening hours and providing services that consider social sensitivities.